Levels of household exposure to solid waste dumpsites and associated loss to health in urban Kenya and Senegal. Issue 1 (2nd January 2022) - Mberu, Blessing; Mutua, Michael; Kabaria, Caroline; Amugsi, Dickson; Muindi, Kanyiva
ABSTRACT: The primary goal of solid waste management to protect the health of the population, particularly low-income groups, has been hindered by lack of local data to pinpoint priorities and identify appropriate interventions across African cities. To fill this gap in order to inform policy and action, this paper examines different levels of exposure to solid waste dumpsites and associated health outcomes in Nairobi, Kenya and Dakar, Senegal. Using representative survey data of households, the study found higher primary exposure of households to the major dumpsite in Nairobi than in Dakar (70% versus 33%, respectively), following the physical proximity of Nairobi municipal dumpsite to large settlements. While there are higher levels of perception of risks to health associated with exposure to dumpsites in Nairobi than Dakar, the linkages between levels of exposure to dumpsites and incidences of morbidities (diarrhea/cholera and respiratory infections) was consistent in the two cities. The protective roles of gender and age of household head in Dakar and the net implications of socio-economic differences, highlight context-specific inputs needed in policy and program interventions. The low incidences of morbidity in Dakar than Nairobi provide empirical evidence supporting the negative health implications of siting dumpsites close to human settlements.